Listerial contamination of raw beef and chevon in north-central Nigeria - Chuku, Aleruchi; Obande, Godwin Attah; Eya, Sani Bashir (IMC Journal of Medical Science, 2020)
Background and objective: Listeria sp. is a ubiquitous and frequently isolated foodborne pathogen. The prevalence of Listeria sp in raw beef and chevon sold in Lafia Nigeria, as well as their antibiotic susceptibility profile was evaluated. Methods: A total 104 samples comprising of 52 raw beef and 52 chevon were obtained from street vendors (hawkers), Shinge abattoir, Lafia old market and Lafia Modern Market. Isolation of Listeria sp. was performed on Listeria Selective Agar, following enrichment in supplemented Listeria Selective Broth. Identification of Listeria sp. was carried out by cultural and biochemical methods. Antimicrobial susceptibility of isolated L. monocytogenes was performed by standard disk diffusion method. Chi-square test was used to determine association between contamination levels at p=0.05. Results: Seven types of Listeria sp. were isolated. L. monocytogenes and L. ivanovii were the most frequently isolated contaminants in all meat types and from all sample sources. L. monocytogenes was isolated with a frequency of 64.4% (67/104) in the meat samples. Beef samples had the highest listerial contamination with a frequency of 58.2% (78/134) compared to chevon which had a listerial frequency of 41.8% (56/134). Resistance of L. monocytogenes to streptomycin and sparfloxacin was 58.2% and 55.2% respectively. Resistance to ampicillin (34.3%) and gentamicin (20.9%) was also observed. Resistances to multiple antimicrobials were detected in 11 L. monocytogenes isolates. Conclusion: The study demonstrated that the raw meat sold in Lafia was contaminated with several Listeria sp. L. monocytogenes showed high rate of resistance to several antimicrobial agents used for the treatment of listerial infection. Appropriate regulation and monitoring of livestock rearing and meat retailing practices are advocated to safeguard the health of consumers. Ibrahim Med. Coll. J. 2019; 13(2): 1-8